Sosialisasi Penerapan Digital Marketing Sebagai Strategi Pemasaran UMKM di Desa Pantai Gading Kabupaten Langkat - Muhammad Ridho Afif; Nurul Hafiza; Dwi; Yaumul Khair Afif; Azhar (peduli riset dan pengabdian masyarakat, 2024)
Technological advancement is the main pillar in today's life, providing innovations that provide positive benefits andfacilitate various aspects of human life. Information technology, especially in the form of digital marketing, is the key toeconomic growth, especially for Micro, Small and Medium Enterprises (MSMEs). However, the use of digital marketing atthe local level such as Pantai Gading Village, Secanggang District, Langkat Regency, is still lacking. The digital marketingsocialisation activity was carried out with the aim of helping MSME players in Pantai Gading Village understand theimportance of digital marketing in increasing sales. Through preparation, socialisation, implementation, monitoring, andevaluation, this activity involved MSME players and was delivered by experts and students. The concept of digitalmarketing, which includes the availability of product information, online interaction, and the utilisation of social media, hasa significant impact on the competitive advantage of MSMEs. While digital marketing offers advantages such as precisetargeting and lower costs, challenges such as potential misuse and negative responses also need to be addressed. Thus,socialisation of digital marketing strategies is important to empower MSME actors with the necessary knowledge and skillsto optimally utilise marketing potential. In the context of Pantai Gading Village, this activity brings hope for local economicgrowth and improved community welfare through increased MSME sales.